The Impact of Invariant NKT Cells in Sterile Inflammation: The Possible Contribution of the Alarmin/Cytokine IL-33 - Ferhat, Maroua Haroun; Robin, Aurélie; Barbier, Louise; Thierry, Antoine; Gombert, Jean-Marc; Barbarin, Alice; Herbelin, André (Frontiers in Immunology, 2018)
Although the contribution of iNKT cells to induction of sterile inflammation is now well-established, the nature of the endogenous compounds released early after cellular stress or damage that drive their activation and recruitment remains poorly understood. More precisely, iNKT cells have not been described as being reactive to endogenous non-protein damage-associated molecular-pattern molecules (DAMPs). A second subset of DAMPs, called alarmins, are tissue-derived nuclear proteins, which are constitutively expressed at high levels in epithelial barrier tissues and endothelial barriers. These potent immunostimulants, which are immediately released after tissue damage, include the alarmin IL-33. This factor has aroused interest due to its singular action as an alarmin during infectious, allergic responses and acute tissue injury, and also as a cytokine, contributing to the latter resolutive/repair phase of sterile inflammation. IL-33 targets iNKT cells, inducing their recruitment in a inflammatory state, and amplifying their regulatory and effector functions. We introduce in the present review a new concept according to which the iNKT cells and IL-33 form a biological axis alerting and controlling the immune cells in experimental models of sterile inflammation. The review will focus on acute organ injury models, especially ischemia-reperfusion injury, in the kidneys, liver and lungs, where iNKT cells and IL-33 have been presumed to mediate and/or control the injury mechanisms, and their potential relevance in human pathophysiology.